Effectiveness of a rational emotive behavior therapy (REBT)-informed group for post-9/11 Veterans with posttraumatic stress disorder (PTSD). Issue 4 (4th July 2021) - Grove, Allen B.; Kurtz, Erin D.; Wallace, Rachel E.; Sheerin, Christina M.; Scott, Sarah M.
ABSTRACT: Various treatments aimed for posttraumatic stress disorder (PTSD) have been developed for Veterans, but many are not formatted for use in groups, do not address common psychiatric comorbidities, and include inherent barriers (e.g., substantial time commitment). This program evaluation study aimed to examine the effectiveness of a five-session treatment, a Rational Emotive Behavior Therapy (REBT)-Informed Group focused on changing irrational beliefs to address comorbid depression and anxiety (as well as anger and guilt) among post-9/11 Veterans with PTSD. Participants ( n = 47) completing the REBT-Informed Group demonstrated significant reductions at posttreatment in depression and PTSD symptoms. Compared to Veterans in a ten-session treatment-as-usual group ( n = 47), there was no significant difference in PTSD symptom improvement despite the reduction in number of sessions. The study demonstrates that a five-week group treatment for PTSD comorbid with depression or anxiety in post-9/11 Veterans – a therapy that may be uniquely suited to a military or Veteran population, but potentially generalizable to civilians as well – can lead to significant reductions in depression and PTSD symptoms. Future directions include development of a manual for dissemination and replication of findings of the REBT-Informed Group to other military or Veterans Affairs medical centers.